Patient safety culture as perceived by intern-ship nursing students - Mohamed, Safaa; Rushdy, Fatma (International Journal of Advanced Nursing Studies, 2017)
Background: Patient Safety Culture is a relatively new concept in health management. Highly reliable health care providers have a patient safety culture incorporated in them. Aim: To assess perception of internship nursing students about patient safety culture during their work-ing at Minia and Assiut Universities Hospitals. Subjects and methods: Descriptive correlation design was utilized for this current study. A convenience sample of nurses' intern, equal both to participate 200 nurse intern from Minia and Assiut Universities Hospitals. The data collected through self-administered questionnaire which includes personal characteristics data and patient safety culture questionnaire. Re-sults: Illustrated the positive correlation between all factors of patient safety culture among internship nursing students in Minia and patient safety level with highly statistically significant differences. There were positive correlations between hospital work area / unit and residence with statistically significant differences. Conclusions: There were positive correlations among studied internship nursing students as regard to the level of patient safety and all factors of patient safety cultures (Hospital work area, your supervisor, Communication, Frequency of events reported, Patient safety at your hospital). Recommendations: Study the association between patient safety culture and quality of care from patients’ perspectives.